Analisis Perbandingan Protokol Routing OSPF dan RIPv2 berdasarkan Variasi Jumlah Router pada Jaringan MPLS dan Tanpa MPLS - Dudy Supriadi; Andi Hidayat Jatmika; I Wayan Agus Arimbawa (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
The wider scope of a network, it cannot be denied that the number of nodes on the network will increase. This of course will affect the performance of the routing protocol used. So it is necessary to do research to determine the performance of the routing protocol used when given the number of routers on the network to be built. In this study the author tries to analyze the comparison of different routing protocols, OSPF and RIPv2 if given variations in the number of routers running on MPLS and without using MPLS Networks in the GNS3 simulator. The research was conducted by simulating networks that have been configured OSPF and RIPv2 routing protocols with MPLS and without MPLS in the GNS3 simulator. Testing is done by taking data as much as ten repetitions by generating UDP packets. In testing given different bandwidth variations. Based on the results of the study, it was found that MPLS technology can improve the performance of the OSPF and RIPv2 routing protocols.